Analysis of hematopathology and alteration of JAK1/STAT3/STAT5 signaling axis in experimental myelodysplastic syndrome. (25th December 2016) - Daw, Suchismita; Chatterjee, Ritam; Law, Aditya; Law, Sujata
Abstract: Hematological disorders like myelodysplastic syndrome (MDS) may arise due to cumulative dysregulation of various signalling pathways controlling proliferation, differentiation, maturation and apoptosis of bone marrow cells. This devastating bone marrow condition can be due to consequential abnormalities in haematopoiesis as well as its supportive microenvironment. Although mutations related to JAK/STAT pathway are common in myeloproliferative neoplasms, further studies are required to fully explore the myelodysplastic scenario regarding the concerned pathway. In this study, we have investigated the JAK-STAT signalling pathway which inevitably plays a crucial role in haematopoiesis. MDS was mimicked in a mouse model with an induction of ENU in adult mice. The bone marrow of the control and MDS groups of animals were subjected to a variety of tests, including cell morphology study in peripheral blood and bone marrow, cytochemistry and histochemistry of bone marrow smears, karyotyping and flowcytometric expression analysis of the phosphorylated forms of proteins like JAK1, STAT3 and STAT5 (denoted as pJAK1, pSTAT3 and pSTAT5) and the phenotypic expression of proteins like CD45 and CD71. The results revealed that the morphology of the blood and bone marrow cells were dysplastic compared to the affected blast populations of different lineages. The expression of common leucocyte antigen CD45 was less in comparison to the expression of transferrin receptor CD71 which was increased in the ENU induced MDS mouse model. Moreover, we have observed an upregulated expression of JAK1 followed by STAT5. Therefore, we can conclude that downregulation of CD45 may have helped in the upregulation of JAK-STAT signaling and CD71 expression. This aberrant signaling may be among one of the activated signaling axes that lead to affected hematopoietic lineages in Myelodysplastic syndrome. Graphical abstract: Highlights: Lower CD45 level was associated with increased JAK1/STAT5 signalling in MDS marrow. JAK1/STAT5 up-regulation may be linked to dysregulated haematopoiesis. STAT5 up-regulation was associated with increased CD71 and erythroid dysplasia.